Detection and characterization of biogenic selenium nanoparticles in selenium-rich yeast by single particle ICPMS. Issue 3 (13th February 2018) - Jiménez-Lamana, Javier; Abad-Álvaro, Isabel; Bierla, Katarzyna; Laborda, Francisco; Szpunar, Joanna; Lobinski, Ryszard
Abstract : The occurrence of SeNPs in commercial Se-rich yeasts was confirmed by SP-ICPMS for the first time. Abstract : A method based on single particle inductively coupled plasma mass spectrometry (SP-ICPMS) was developed for the analysis of commercial Se-rich yeasts, to confirm the occurrence of selenium nanoparticles in these food supplements. A considerable reduction of background levels was achieved by combining data acquisition at microsecond dwell times and the use of a H2 reaction cell, improving by a factor of 10 the current state-of-the-art methodology, and bringing size detection limits down to 18 nm for selenium nanoparticles. The presence of nanoparticulate selenium was revealed by size-exclusion chromatography ICPMS, with detection of a selenium peak at the exclusion volume of the column showing absorption at a wavelength corresponding to selenium nanoparticles. SP-ICPMS allowed us to confirm the presence of Se-nanoparticles, as well as to calculate the nanoparticle size distribution, from information about the shape and elemental composition of the nanoparticles obtained by transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS), respectively. These results reveal the significance of nanoparticles in the speciation of metals and metalloids in biological samples and the capability of SP-ICPMS in combination with TEM-EDS to carry out these analyses.